Epigenetic stability of exhausted T cells limits durability of reinvigoration by PD-1 blockade - Pauken, Kristen E; Sammons, Morgan A; Odorizzi, Pamela M; Manne, Sasikanth; Godec, Jernej; Khan, Omar; Drake, Adam M; Chen, Zeyu; Sen, Debattama R; Kurachi, Makoto; Barnitz, R Anthony; Bartman, Caroline; et al. (Science (American Association for the Advancement of Science), 2016)
Blocking Programmed Death-1 (PD-1) can reinvigorate exhausted CD8 T cells (T ) and improve control of chronic infections and cancer. However, whether blocking PD-1 can reprogram T into durable memory T cells (T ) is unclear. We found that reinvigoration of T in mice by PD-L1 blockade caused minimal memory development. After blockade, reinvigorated T became reexhausted if antigen concentration remained high and failed to become T upon antigen clearance. T acquired an epigenetic profile distinct from that of effector T cells (T ) and T cells that was minimally remodeled after PD-L1 blockade. This finding suggests that T are a distinct lineage of CD8 T cells. Nevertheless, PD-1 pathway blockade resulted in transcriptional rewiring and reengagement of effector circuitry in the T epigenetic landscape. These data indicate that epigenetic fate inflexibility may limit current immunotherapies.